2021
DOI: 10.1186/s42825-021-00056-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of strain and filtration properties of a semi-finished leather product

Abstract: A study on deformation and filtration properties of a leather semi-finished product after chrome tanning are presented. The analytical dependences of compressive load on compressive (recovery) strain and moisture content of a leather semi-finished product are obtained. The empirical dependences of hydraulic gradient on filtration rates are determined for various compression ratios of the leather semi-finished product. It was revealed that with an increase in compressive load and moisture content of the leather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…To lead to the main result of the proposed article, attention is focused on an exceptional methodological approach [12][13][14][15][16][17][18][19][20] based on the analysis of derivatives of input and output signals that are available for measurement. This method represents a unique and innovative way that provides compelling evidence of the effectiveness and feasibility of our new control algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…To lead to the main result of the proposed article, attention is focused on an exceptional methodological approach [12][13][14][15][16][17][18][19][20] based on the analysis of derivatives of input and output signals that are available for measurement. This method represents a unique and innovative way that provides compelling evidence of the effectiveness and feasibility of our new control algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…According to studies carried out in [34,38,39], the deformation properties of skin are described by power-law dependences…”
Section: Resultsmentioning
confidence: 99%
“…The properties of leather/collagen, such as thermal stability and physical properties, are closely correlated with their water content [2,3]. Schroepfer investigated the thermal stability of untanned and tanned bovine collagen with different hydration degrees by using differential scanning calorimetry (DSC) and confirmed that crosslinking degrees and drying increased the denaturation temperature of bovine hide collagen [4].…”
Section: Introductionmentioning
confidence: 97%